KESIAPAN KECAMATAN DALAM MENERIMA DAN MELAKSANAKAN PELIMPAHAN SEBAGIAN KEWENANGAN PEMERINTAHAN DARI BUPATI KEPADA CAMAT DI KABUPATEN CIANJUR PROVINSI JAWA BARAT - Riswati Riswati; Muslim Muslim (Jurnal Ilmiah Wahana Bhakti Praja, 2016)
AbstractStructuring the territory understood as a method and not a fi nal destination in the structure ofgovernance (local). The ultimate goal in governance or regional government is the achievementof social welfare. Structuring the region as a method intended to bring the device to the localcommunity as the owner of sovereignty.Sub-District as a working area of the district head has an important position in the publicservice, because it deals directly with the public as the main consumers of public services inquestion. Important essence of districts explicitly stated in Law No. 32 of 2004, which confi rmedthat the sub-district serves as the district/city.This research uses descriptive research design analysis with a qualitative approach. This studyincludes qualitative research, which produces descriptive data. Qualitative research is alsomore emphasis on process rather than in terms of results, in addition to this research mayreveal a problem concerning what is in accordance with the reality on the ground.Based on the results of research and discussion as well as the data obtained in the fi eld,it can be concluded as follows: 1) decree No. 44 and No. 45 of 2012 issued on December28, 2012 have not been fully implemented. The Regent of new regulations implemented infour districts as a pilot project for the District Campaka and Cidaun representing southerncoastal areas Cianjur berkarateristik ocean regions and the mainland. While CematanPacet and Middle Reef representing the Highlands and the Regional Tourism; 3) Basedon the results of questionnaires distributed researchers showed that almost 94% of theauthority delegated by declaring that have been implemented by the Head Campaka,Cidaun, Karangtengah and Pacet despite many obstacles. 4) Based on the interview withthe Head Campaka, Cidaun, Karangtengah and Pacet and the districts mentioned thatthe authority delegated in accordance with Law No. 32 of 2014 governing authority of theRegent. But the delegation of authority was not followed denganpembiayaan suffi cient; 5)Obstacles encountered in the implementation of devolved government affairs, among others,the allocation of funds from the budget has been no improvement since the publication oflegislation or declaring the partial delegation of authority so that what is being implementedby kecamaatan still in accordance with the regulations and declaring before it was issued.Another was in the delegation of authority should be delegated the funds and personnel aswell as the completeness of facilities and infrastructure to carry out the delegated authority;Of the conclusions that can be drawn up by the author, the author tries to give somerecommendations, among others: 1) the ineffectiveness of the role and function of districts foris probably due to the limited authority given to districts to districts that causes districts “nothesitate” to take action if social problems arising in the areas they work; 2) In addition, untilnow there is no synchronization of activity between districts and other institutions at the districtlevel (vertical and horizontal); 3) Short-term: through the synchronization of activities andmake districts as an important actor in the management of these activities, the medium term:to simplifi cation institutions where local authorities through applicable legislation activate therole and functions of the district. Long-term: to reduce the role and function of districts to onlyfocus on one function, namely the function of public services. But we realize that this causes motion districts arena becomes very, very limited, while the other functions being in the arena of motion districts.Keywords: government, delegation of authority and district